2020
DOI: 10.1136/medethics-2019-105472
|View full text |Cite
|
Sign up to set email alerts
|

Should free-text data in electronic medical records be shared for research? A citizens’ jury study in the UK

Abstract: BackgroundUse of routinely collected patient data for research and service planning is an explicit policy of the UK National Health Service and UK government. Much clinical information is recorded in free-text letters, reports and notes. These text data are generally lost to research, due to the increased privacy risk compared with structured data. We conducted a citizens’ jury which asked members of the public whether their medical free-text data should be shared for research for public benefit, to inform an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…Notably, the opt-out is only a meaningful way of ensuring individual autonomy if transparency of data usage, and stakeholder inclusion, is guaranteed. This combination (opt-out plus full transparency) is also the public’s preferred approach 53, 54 , and is thus vital for maximising public trust, and securing a social licence, for any initiative. One example of operationalising a transparent patient opt out was launched by the NHS in the UK in May 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the opt-out is only a meaningful way of ensuring individual autonomy if transparency of data usage, and stakeholder inclusion, is guaranteed. This combination (opt-out plus full transparency) is also the public’s preferred approach 53, 54 , and is thus vital for maximising public trust, and securing a social licence, for any initiative. One example of operationalising a transparent patient opt out was launched by the NHS in the UK in May 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Biobanking participants generally have limited understanding of the aspects of research included in consent forms, and the level of understanding depends on contextual and demographic factors such as education [ 49 ]. A recent deliberative study showed that better informed persons are more supportive of sharing data for health research [ 50 ]. As such, improving research participants’ knowledge on data protection processes (e.g., through public engagement, increased transparency or more extensive consent procedures) might enhance autonomy but also improve patient trust.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients should be involved as key stakeholders throughout all stages of the research process. The public also expects that researchers are committed to a culture of continuous improvement of methods for coding, anonymizing, processing, and safeguarding clinical free-text data [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited via advertisements on the Healtex website. The workshop was attended by 44 people and included outlines of the TexGov study aims, the findings of a previous citizens’ jury on using clinical free-text data for research [ 15 ], and data protection. These were followed by presentations from the NLP community on their approaches to working with clinical free-text data, during which the audience was asked to write down the topics to discuss in more detail.…”
Section: Methodsmentioning
confidence: 99%